(untitled) - Munir, Arslan (New York, 2016)
This book introduces the state-of-the-art in research in parallel and distributed embedded systems, which have been enabled by developments in silicon technology, micro-electro-mechanical systems (MEMS), wireless communications, computer networking, and digital electronics. These systems have diverse applications in domains including military and defense, medical, automotive, and unmanned autonomous vehicles.
Keywords: Xử lý dữ liệu điện tử,Parallel processing (Electronic computers),Electronic data processing,Xử lý song song (máy tính điện tử); Distributed processing